Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
William Raleigh Watkins (7/1832-2/22/1891) grandfather of Estelle Watkins Morgan; Union soldier fought in Battle of Missionary Ridge 11/24/1863 GGGrandson of Thomas Watkins; Thomas was Alberts GGGGrandfather